Utilization of microalgae in green context :|adsorptive removal of ionic contaminants from aqueous media and production of microalgal bioplastics - Özgümüş, Beste. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Microalgae are known for their remarkable growth rates and adaptation capa bilities. In this study, microalgae were used as environmentally friendly materials for two diﬀerent applications. The ﬁrst part is focused on removal of dyes from aqueous media using microalgae as adsorbents. Nile blue, methylene blue, eriochrome black t, and congo red are used as model charged contaminants. Seven microalgae species were used either immobilized in hydrogels or in free forms. Two of best cationic dye adsorb ing species, Chlorella and Scenedesmus were selected for further experiments. Eﬀects of growth period and Ca2+ deprivation on dye removal was studied. In kinetic exper iments employing Chlorella, pseudo-ﬁrst order, pseudo-second order and intraparticle diﬀusion models were employed for the interpretation of resulting data. Langmuir, Fre undlich and Temkin models were used to ﬁt resulting adsorption isotherms. Moreover, FT-IR analysis was conducted on these microalgae before and after dye adsorption. In the second part, a type of cyanobacteria Spirulina-based biodegradable plastic ﬁlms were prepared in diﬀerent formulations by casting method. Films were char acterized by tensile tests and zeta potential measurements. Spirulina was used in Spirulina/PVA blends in the absence or presence of several concentrations of micro bial Transglutaminase as crosslinker. Spirulina was also tested as the single matrix with several concentrations of plasticizer and the enzyme. Additionally, proteins were extracted from Spirulina and ﬁlms were prepared using this extract, modiﬁed or not modiﬁed with microbial Transglutaminase.
Keywords: Microalgae.